1993
DOI: 10.1093/rheumatology/32.10.903
|View full text |Cite
|
Sign up to set email alerts
|

Twin Concordance Rates for Rheumatoid Arthritis: Results From a Nationwide Study

Abstract: We report the concordance rate for RA in a nationwide study of 91 monozygotic (MZ) and 112 dizygotic (DZ) pairs. Twin pairs were recruited from both a national media campaign and a 2-month prospective inquiry of all UK rheumatologists. Disease status was established following a structured clinical and serological appraisal, together with radiological assessment where necessary. Zygosity was confirmed using DNA fingerprinting. In all, 14 (15.4%) of the MZ and four (3.6%) of the DZ pairs were disease concordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
260
0
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(277 citation statements)
references
References 0 publications
6
260
0
11
Order By: Relevance
“…1 Although RA and SLE are considered as idiopathic diseases, both the higher concordance rates and familial aggregation indicate a significant genetic influence on their pathogenesis. [2][3][4] Human leukocyte antigen genes are the strongest genetic locus known to be associated with susceptibility to both diseases. 5,6 Nevertheless, genome-wide linkage studies have shown several non-human leukocyte antigen loci influencing their susceptibility risk.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although RA and SLE are considered as idiopathic diseases, both the higher concordance rates and familial aggregation indicate a significant genetic influence on their pathogenesis. [2][3][4] Human leukocyte antigen genes are the strongest genetic locus known to be associated with susceptibility to both diseases. 5,6 Nevertheless, genome-wide linkage studies have shown several non-human leukocyte antigen loci influencing their susceptibility risk.…”
Section: Introductionmentioning
confidence: 99%
“…1 Twin concordance rate analyses and recently genome scan analyses give important insights into the genetic background of RA. [2][3][4][5][6] The QK(R)RAA shared epitope that is present in HLA DRB1*0401, DRB1*0101, and DRB*0404 genotypes is associated with the occurrence of RA, extraarticular manifestations, and a more severe course of RA. 7 This observation is suggestive of an important role for adaptive immune processes, and in particular for the interaction of antigen presenting and T cells in RA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…mean concordance rate of 12% in monozygotic twins, 4 times higher than in dizygotic twins (3)(4)(5)(6). Our group (the European Consortium on Rheumatoid Arthritis Families [see Appendix A]), a Japanese group, the North American Rheumatoid Arthritis Consortium, and a British group have performed genome scans with different marker sets and an average marker spacing ranging from 10 cM to 12 cM (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%